The governance of imported 2019-nCov infections: What can be learned from China's experience? - Hao Li; Jiaxin He; Jiayu Chen; Shuning Pan; Jiehan Feng; Shuang Liu (BMC, 2022)
Abstract Delta and Omicron variants of 2019-nCoV are still spreading globally, and many imported infections have been identified in China as well. In order to control the spread chain from imported to local, China has implemented the dynamic Covid-zero policy. In this article we summarized China's governance models and practices of fighting potential imported infections in two directions. One targets at international travelers, which can be outlined as four lines of defense: customs epidemic prevention, quarantine upon arrival, relevant laws and regulations, and community tracking. The other is against other vectors potentially carrying 2019-nCoV, which can be outlined by three lines of defense: customs epidemic prevention, disinfection and personal protection, and information management. However, there are still some challenges that are yet to be addressed, such as illegal immigration, accidental occupational exposure to 2019-nCoV, etc. China's experience indicates that no country can stay safe during the global pandemic as long as there are local outbreaks in other countries, and active prevention and control measures based on science and a complete set of laws and regulations are still necessary at current stage. What's more, accountable government commitment and leadership, strengthened health and social governance systems, and whole society participation are required. It is suggested that the global community continue to closely cooperate together and take active rather than passive actions to block the potential imported 2019-nCoV from causing local spreading.